Kollektivierung und Opt-Out Die neue Grundnorm des Urheberrechts? - Modelle im Vergleich: Google Books Settlement, §1371 UrhG, Richtlinie Orphan Works und die Wahrnehmungsbefugnis der VG Wort - Hohlefelder, Olaf (Universitätsverlag Göttingen, 2015)
The German Copyright Law grants an absolute right to authors, i.e., any use of protected works requires the author's prior consent. This concept is known as opt-in. In this doctoral thesis the author examines five models which turn this concept upside down as they provide for the permission for certain beneficiaries to use protected works without the author's prior consent until the author objects to such use. This concept is known as opt-out. Also, the examined models contain elements of collectivization and, in particular, involve collecting societies. The author examines and compares these models and answers the question whether the underlying opt-out concept together with collectivization may be generalized so that it could replace opt-in.